(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
اقترح ترميز تربو كنظام ترميز قناة يُكسب ترميزات قريبة جداً من نهاية سعة قناة شانون " Shannon"، ويُقدّم أداءاً مُميّزاً بسبب استعماله لطرق جديدة مختلفة عن تقنيات نظرية الترميز العادية. نُقدّم بهذا البحث مقارنة لأداء ترميزات تربو الصندوقية والتلفيفية عبر قناة ضجيج غاوس الأبيض الجمعي(AWGN)، وقناة خفوت Rayleigh باستعمال MATLAB . حيث يلاحظ أن أداء ترميز تربو التلفيفي أفضل بقليل في منطقة التساقط وربح الترميز يكون من 0.5dB إلى 0.7dB عندما يكون معدّل خطأ الخانة ) (BER= ويعتمد على شروط القناة. لكن عندما يكون (BER) أدنى من أو ، فإنه يحدث خطأ قاع في حالة ترميز تربو التلفيفي. أما ترميزات تربو الصندوقية، فإن أدائها أفضل من ترميزات تربو التلفيفية عندما يكون (BER) منخفضاً. نقدّم أيضاً، دراسة للمرمّزات المكوّنة لترميز تربو التلفيفي، ونقترح مرمّزاً أمثل يُكسب أداء خطأ قاع جيد في حالة ترميز تربو التلفيفي. وأخيراً، يتم تصميم ترميز تربو باستعمال المرمّز الأمثل المقترح باستعمال MATLAB وتحليل أدائه. Turbo code is recommended as a channel coding scheme, which has been shown to be capable of performing close to the Shannon limit. In this paper, we compare the performance of both convoluted and block turbo codes over AWGN and Rayleigh fading channels. It has been observed that the performance of convoluted turbo code is slightly better in the rainfall region, and the coding gain ranges between 0.5 and 0.7 dB at BER ofdepending on the channel conditions. But below BER ofor an error floor occurs in the case of convoluted turbo code. When BER is low, Block turbo codes tend to outperform convoluted turbo codes. Then, we propose an optimal encoder for achieving the best error-floor performance in the case of convoluted turbo code. Finally, using the optimal encoder, we present a turbo code design, utilizing MATLAB and analyzing its performance.